The Effect of Intrinsic Motivation on Employee Performance: A Systematic Literature Review - Sulistamtama, Muhammad Faried; Setiawan, Raditya; Yuniawan, Ahyar (LifeSciFi, 2024)
This research was conducted is to analyse the influence of intrinsic motivation on employee performance through Systematic Literature Review. The main problem addressed in this study is how the analysis method and indicators of intrinsic motivation significantly affect employee performance. To answer these problems, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method was used with the help of Watase Uake tools to select and identify relevant journals. The study showed that intrinsic motivation plays an important role in improving employee performance, work engagement, and innovation in the work environment. Key findings include the importance of a supportive work environment, including autonomy, positive interpersonal support, servant leadership, and high-performance work systems that play a role in increasing intrinsic motivation and employee productivity. In addition, cultural values and aspects of spirituality are shown to be significant mediators in the relationship between intrinsic motivation and performance, especially in certain contexts. This study offers a comprehensive view of the importance of management strategies that focus on intrinsic motivation to improve organizational performance and competitiveness across various industry sectors. This approach is expected to provide a basis for the development of more effective management policies in creating a work environment that is more effective for the organization.